Eja - Fshazi, Falma (Die Keure, 2016)
"This dual-narrative, part photo-novel, part real-life journey, tells one story in multiple ways. In its first part, the book couples short stories by Falma Fshazi with photographs by Stefano Graziani. The story of a discovery; an encounter with a strange land, beyond East and West, and a city, Tirana. The second part casts a restrospective look at the construction of a tower designed by 51N4E, and on all the projects that followed in its wake, from 2004 onwards. It describes moments, processes and relationships that allowed the architects to come into contact with a culture and a context so different from their own. Overall, this book is a story of embracing otherness, and a contemplation on how things meet"--Back cover. - "How Things Meet' takes a retrospective look at the construction of 51N4E’s TID tower in Tirana (ALB) and explores the projects that followed in its wake. In addition, the book marries Falma Fshazi’s short stories about discovering Tirana. Photographs by Stefano Graziani." --51N4E
Keywords: 51N4E (Firm); Hotels / Albania / Tirana / Fiction; Hotels / Albania / Tirana; Architecture / Albania / Tirana / History; Architecture; Buildings; Hotels; Hochbau; Hotel; Hochhaus; Stadtleben; Tirana (Albania) / Buildings, structures, etc / Fiction; Tirana (Albania) / Buildings, structures, etc; Tirana (Albania) / Buildings, structures, etc / Pictorial works; Albania / Tirana; Tirana; TID Tower -- Tirana; Bildband